Att instruera i idrottskontext - Katarina Lundin (Educare)
This article investigates language use in sports, and more specific how trainers address their young trainees in athletics, jujutsu, and gymnastics. The article focuses the instructions that the trainees receive when performing different exercises during training. The primary theoretical framework is Bernstein’s (1971 and onwards) concepts classification, framing, and a collective as opposed to an integrated code, concepts which are otherwise used in other contexts. Against this theoretical background, the trainers’ language use is analyzed. In brief, the results show that the trainers’ language for instructions can be described as a collective code, due to a strong classification and a strong framing. This has impact on and at the same time is the result of the trainers’ language use.